Picosecond laser-driven terahertz radiation from large scale preplasmas of solid targets. (May 2016) - Liao, G Q; Li, Y T; Li, C; Su, L N; Zheng, Y; Liu, M; Dunn, J; Nilsen, J; Hunter, J; Wang, W M; Sheng, Z M; Zhang, J
Abstract: The terahertz (THz) radiation from the front of solid targets with a large-scale preplasma irradiated by relativistic picosecond laser pulses has been studied. The THz radiation measured at the specular direction nonlinearly increases with laser energy and an optimal plasma density scalelength is observed. Particle-in-cell simulations indicate that the radiation can be attributed to the model of mode conversion. While the THz radiation near the target normal direction is saturated with laser energy and plasma scalelength. Unlike the radiation in the specular direction' the transient current formed at the plasma-vacuum interface could be responsible for the radiation near the target normal.